Category of Power on the States Geostrategy - Yatsenko, B. P. (Ukrainian Geographical Journal, 2025)
The political sciences of the 20th century, as defined by Max Weber (1976), dominate the concept of “power.” Previously, Friedrich Nietzsche (1880) emphasized the significance of the idea of “power” in social life. Presently, in the field of political geography and geopolitics, four variations of “power” are being investigated: economic, military, “soft,” and “smart” powers. Resources that are forming, behaviors, primary currencies, and policies of the governments of individual states are entirely different, but various “powers” joining and interacting attain the integral effect of geostrategic positioning of specific countries. In the leading, highly developed countries of the world, multiple compositions of different varieties of “power” are formed. In other countries, the processes of geoeconomic and geopolitical positioning continue. A deep-rooted connection to the national culture and the fundamentals of glory and will of the Ukrainian nation enables the Ukrainian state to look to the future with optimism.